The Effect of Examining Actual Products or Product Descriptions on Consumer Preference - McCabe, Deborah Brown; Nowlis, Stephen M. (Journal of Consumer Psychology, 2003)
Many consumers purchase products in stores, where they can physically examine and touch the items. In addition, consumers shop for products online or through direct mail, where they cannot physically examine and touch the merchandise. Building on an analysis of perceptual mechanisms involved in the sense of touch, we find that products with primarily material properties, such as clothing or carpeting, are more likely to be preferred in shopping environments that allow physical inspection than in those environments that do not. We also find that there is no difference in preference across the two environments for products with primarily geometric properties, such as packaged goods, for which vision is highly diagnostic. Furthermore, when the touch properties of a material product are verbally described, this reduces the difference in preference between the two environments.